AgNPs Functionalized with Dithizone for the Detection of Hg2+ Based on Surface-enhanced Raman Scattering Spectroscopy - Guo, Na; Xu, Guangda; Zhang, Qijia; Song, Peng; Xia, Lixin (Plasmonics (Norwell, Mass.), 2022)
Mercuric ion (Hg 2+ ), a poisonous metal ion that remained in water ecosystems, can severely damage the human central and peripheral nervous system and kidneys. Consequently, rapid and highly sensitive methods to determine trace Hg 2+ are meaningful to discuss. In recent years, methods for detecting heavy metals by complexation reactions have emerged one after another. We have proposed a novel approach of surface-enhanced Raman scattering (SERS) for the quantitative analysis of Hg 2+ in water samples using dithizone (DTZ) as a Raman reporter. DTZ-modified silver nanoparticles (AgNPs) produced a strong SERS signal. In the presence of Hg 2+ , the DTZ can capture Hg 2+ composing a stable structure, resulting in DTZ leaving the surface of the AgNPs, with an accompanying decrease in the signal. The proposed SERS assay showed a linear range of 10 –4 –10 –8 M, with a limit of detection of 9.83 × 10 –9 M. The sensor has low detection cost, rapid detection speed, and uncomplicated sample pretreatment. Furthermore, this method can be successfully utilized to detect Hg 2+ rapidly in water samples, which sheds new light on the detection of Hg 2+ in the environment.